Synthesis of Poly[(3-(6-(9-anthracenylmethoxy)hexyl)thiophene)-co-(3-(6-bromohexyl)thiophene)] Postfunctionalized from Poly(3-(6-bromohexyl)thiophene): A Comparative Study of the Base Polymer with Its Chlorinated Analogous - F. R. Díaz-Alzamora; M. A. del Valle; C. M. Núñez; P. P. Zamora; J. P. Soto; J. C. Bernède (International Journal of Polymer Science)
A synthetic method based on the postfunctionalization of a reactive homopolymer precursor, which allows for the preparation of different copolymers derived from poly(3-alkylthiophene), was studied. Although these groups decrease the solubility of the resultant material, they enable controlling the degree of substitution to obtain a material with improved spectroscopic (absorption and emission) properties making them useful for the fabrication of electronic devices, for example, solar cells and light-emitting diodes. Furthermore, a comparative study of two halogenated (Cl and Br) reactive poly(3-ω-haloalkyl)thiophenes was carried out.